The region matters—for whom? The regional actor network for vocational education and training in tourism of Cancún (Mexico) - Natascha Röhrer; Beke Vogelsang; Martina Fuchs (International Journal of Training and Development, 2021)
Actor networks are relevant to provide vocational education and training. Many studies have focused on such networks without a clear regional focus. Suggesting a conceptual approach of regional actor networks based on contributions of business education and economic geography, this study analyses the regional actor network in the tourism sector in Cancún (Mexico). Methodologically, the study follows an exploratory qualitative approach. The results illustrate that there are two dominant axes within the regional network, which comprise on the one hand hotels cooperating with applied universities, and on the other hand hotels cooperating with vocational schools. This local actor network has impacts on the practical relevance that vocational education and training provides to the learners, and generates a particular, and rather vulnerable, way of regional development.
Keywords: 650